2022
DOI: 10.1111/nph.18462
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drought on grassland phenology depend on functional types

Abstract: Shifts in flowering phenology are important indicators of climate change. However, the role of precipitation in driving phenology is far less understood compared with other environmental cues, such as temperature.We use a precipitation reduction gradient to test the direction and magnitude of effects on reproductive phenology and reproduction across 11 plant species in a temperate grassland, a moisture-limited ecosystem. Our experiment was conducted in a single, relatively wet year. We examine the effects of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Experimental studies (Henry and Molau, 1997;Price and Waser, 1998;Menzel and Fabian, 1999;Botta et al, 2000;Fu et al, 2015;Malyshev, 2020) have shown that air temperature is the main driver of phenological changes in northern temperate and highlatitude regions. In addition, precipitation has an impact on the spring phenology of grasslands (Shen et al, 2018;Castillioni et al, 2022). In the temperate grasslands of China, the effects of daytime and nighttime temperatures on spring phenology are asymmetric, with the monthly average maximum temperature having a greater effect in winter and the monthly average minimum temperature causing a greater effect in spring (Shen et al, 2018).…”
mentioning
confidence: 99%
“…Experimental studies (Henry and Molau, 1997;Price and Waser, 1998;Menzel and Fabian, 1999;Botta et al, 2000;Fu et al, 2015;Malyshev, 2020) have shown that air temperature is the main driver of phenological changes in northern temperate and highlatitude regions. In addition, precipitation has an impact on the spring phenology of grasslands (Shen et al, 2018;Castillioni et al, 2022). In the temperate grasslands of China, the effects of daytime and nighttime temperatures on spring phenology are asymmetric, with the monthly average maximum temperature having a greater effect in winter and the monthly average minimum temperature causing a greater effect in spring (Shen et al, 2018).…”
mentioning
confidence: 99%
“…Our study found that N addition delayed reproductive phenology and shortened the reproductive period at the community level, which is in contrast to previous reports that N addition significantly prolonged flowering and fruit‐set durations at the species level on the Tibetan Plateau (Shen et al, 2022; Xi et al, 2015). This difference in results may be due to differences in the direction and magnitude of phenological changes within the community, offsetting effects at the species and functional group levels (Castillioni et al, 2022; Meng et al, 2016). We observed that under N addition this community‐level phenological response pattern was attributed to a significant delay in the onset of budding and flowering in early‐flowering sedges and to an advanced end of flowering and fruiting in late‐flowering forbs (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Any phenological differences in plant functional groups may alter the relative fitness among members of the community, which in turn affects community composition (Castillioni et al, 2022). However, phenological responses to N enrichment and precipitation changes are often at the specific-species level (focused on a few common species) (Liu et al, 2021;Liu, Monaco, et al, 2017;Xia & Wan, 2013), with no clear responses of specific functional groups (Prevey et al, 2019), which exacerbates the difficulty of assessing plant phenological changes under ongoing N enrichment and precipitation changes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations